A systematic review and meta‐analysis of music therapy for the older adults with depression. (19th April 2016) - Zhao, K.; Bai, Z.G.; Bo, A.; Chi, I.
Abstract : Objectives: To determine the efficacy of music therapy in the management of depression in the elderly. Method: We conducted a systematic review and meta‐analysis of randomized controlled trials. Change in depressive symptoms was measured with various scales. Standardized mean differences were calculated for each therapy–control contrast. Results: A comprehensive search yielded 2, 692 citations; 19 articles met inclusion criteria. Meta‐analysis suggests that music therapy plus standard treatment has statistical significance in reducing depressive symptoms among older adults (standardized mean differences  = 1.02; 95% CI = 0.87, 1.17 ). Conclusions: This systematic review and meta‐analysis suggests that music therapy has an effect on reducing depressive symptoms to some extent. However, high‐quality trials evaluating the effects of music therapy on depression are required. Copyright © 2016 John Wiley & Sons, Ltd.